Effectiveness of Using the Science, Technology, Engineering, and Mathematics (STEM) Approach in Developing Higher-Order Thinking Skills: A Meta-Analysis - AlGhamdi, Reem A. (Journal of Ecohumanism, 2025)
This study investigated the effectiveness of the Science, Technology, Engineering, and Mathematics (STEM) approach in developing higher-order thinking skills and examined whether its impact varied according to teaching model, educational stage, field of study, gender, sample size, or learning environment. A meta-analysis was conducted on 35 primary studies published between 2015 and 2025 that employed STEM to enhance higher-order thinking skills among learners across different educational levels. Data were coded using a specially designed coding sheet, and 37 effect sizes were calculated using Hedges’ g index to ensure accuracy. Analyses included heterogeneity testing, publication bias assessment, and subgroup comparisons, conducted with Comprehensive Meta-Analysis software (v4) and Microsoft Excel. Results indicated a strong overall effect of STEM on higher-order thinking skills under the random-effects model, with a combined mean effect size of ES = 0.97, SE = 0.085, and a 95% confidence interval of 0.805–1.14. The corresponding percentage value of the combined effect was 33%. Subgroup analysis showed that the STEM approach consistently improved higher-order thinking skills regardless of contextual variables. Accordingly, the study recommends integrating STEM pedagogy into both pre-service and in-service teacher education and training programs to foster higher-order cognitive skills.